Pengaruh Penggunaan Media Sosial Facebook Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Geografi - Rati Ratna Sari; La Ode Amaluddin; Andrias (Jurnal Penelitian Pendidikan Geografi, 2023)
Along with the development of technology, the use of social media is also increasingly intense, however, the rapid development of technology among students cannot be separated from the positive and negative impacts it has. The purpose of this study was to analyze the effect of the use of Facebook social media on student learning outcomes in Geography class XI IPS Senior High School 2 Wangi-Wangi. Simple linear regression analysis was used in this study to explain the relationship between Facebook social media use and learning outcomes. The results showed that the t-test value = -0.666 < t table and the coefficient of determination r2 = 0.018, which means that the contribution of the influence of the use of social media Facebook on learning outcomes is 0.18% and 0.82% is influenced by other factors. The statistical results show that there is no significant effect of the use of Facebook social media on student learning outcomes in Geography class XI IPS at Senior High School 2 Wangi-Wangi.